Determination of the required hydrophilic-lipophilic balance for the development of emulsions containing turpentine oil (Research, Society and Development, 2024)
Emulsions are versatile formulations used across various industrial sectors; in pharmacy and cosmetology, they are referred to as "lotions." These emulsions are created by combining two immiscible liquids, a process made possible by the addition of a surfactant. This compound has both polar and non-polar functional groups in molecular structure, which position themselves between the hydrophilic and hydrophobic components, respectively, forming micelles. Due to the complexity and potential instability of this system, producing emulsions resistant to phase separation, especially when using vegetable oils, requires determining the hydrophilic-lipophilic balance (HLB) needed for such formulations. The HLB system classifies surfactants based on their solubility in water and oil. To determine the HLB required for emulsions containing turpentine oil, we applied a serial emulsion production methodology. The result was the formulation and production of 42 emulsions, each with a required surfactant concentration of 15% and an HLB value of 8.15, which aligns with the qualitative evaluations and stability tests conducted in this study.